ANALYSIS OF THE BUSINESS ECONOMICS OF DUCKLINGS IN LANGKAT REGENCY - Muhammad Buchari Sibuea (JASc (Journal of Agribusiness Sciences), 2017)
The research was conducted in Pematang Cengal Barat Village, Tanjung Pura Sub-district, Langkat Regency, to identify and know the availability of production input, business management system, the amount of business income and the contribution of the broiler duck business income to the overall income which also works as rice farmer. The research area is determined purposively considering the typical characteristics of this business. The population of 30 people used as a sample of research. The data obtained were analyzed descriptively. From the result of the research, it is found that proportional availability of input or production factor for this business is quite good. While the business management system of broiler duck is still done simply and traditionally but showed better results. Revenue earned by broiler ducks is quite high per season and even the contribution of this broiler duck to total income than farmers is bigger than their main business from rice farming.The results recommend that farmers make livestock business as the main business which maintenance can be done extensively and intensively so as to produce good productivity.Keywords: economic analysis, broiler duck